Evaluating Large Language Model Versus Human Performance in Islamophobia Dataset Annotation - Rafizah Daud; Nurlida Basir; Nur Fatin Nabila Mohd Rafei Heng; Meor Mohd Shahrulnizam Meor Sepli; Melinda Melinda (The Science and Information Organization (SAI), 2026)
Indexed by (Tier 2)